A Case Report On The Effect Of Jalaukavacharana In A Chronic Non-Healing Wound (Dushta Vrana) - Ranjan, Priya; Verma, Deepali Sundari (Journal of Neonatal Surgery, 2026)
Chronic non-healing wounds represent a significant clinical challenge due to delayed tissue repair, persistent inflammation, and compromised local circulation. In Ayurveda, such wounds are described under Dushta Vrana, wherein vitiation of Rakta and Pitta plays a pivotal role in delayed healing. Jalaukavacharana (leech therapy), a parasurgical procedure classified under Raktamokshana, is indicated in conditions associated with Rakta–Pitta Dushti and is traditionally known for its blood-cleansing, anti-inflammatory, analgesic, and wound-healing effects.This case report documents the successful management of a chronic non-healing wound of four years’ duration using Jalaukavacharana in combination with appropriate Ayurvedic local wound care and internal medications. Medicinal leeches were applied around the wound margins under aseptic precautions, followed by standard wound cleansing and dressing. The treatment protocol was administered systematically with regular follow-up.Progressive improvement was observed in terms of reduction in pain, inflammation, discharge, and wound size, along with healthy granulation tissue formation. Complete wound healing was achieved within eight weeks of treatment, with no recurrence or adverse effects noted during the follow-up period.The outcome of this case highlights the potential role of Jalaukavacharana as a safe, effective, and economical therapeutic modality in the management of chronic non-healing wounds. When used judiciously as part of an integrative Ayurvedic treatment approach, it can offer promising results in long-standing and refractory cases of Dushta Vrana...